Compare Different Blood Parameters Between Different Types of Cathete in Atherosclerosis Patients with Type 2 Diabetus - A. Ibrahim, Suhad; A. Zainulabdeen, Jwan; M. Jasim, Hameed (Al-Nahrain Journal of Science, 2021)
Human blood groups ABO (BG) represent an important system in blood transfusion medicine and transplantation, and have a role in the development of heart disease. The current study was conducted with the aim of comparing the types of blood groups and knowing the most affected by atherosclerosis and type 2 diabetes. Our study was consisted of total (n=192) population with age range (45-70) years old and overweight in terms of their BMI. The first group included (n=64) under Precautinous coronary intervention (PCI) catheterization with atherosclerosis and diabetes type 2. The second group (n=64) underwent Diagnostic (DIG) catheterization with diabetes type 2 and without atherosclerosis. The association between blood group types with diabetes type 2 disease and atherosclerosis was investigated. The most prevalent blood group was O+ (93.74%) in DIG, (80.84%) in PCI closely followed by group B (49.99%), (44.62%) in DIG and PCI respectively, and group A (43.75%) In both group. Least prevalent blood group was AB (35.25%) in PCI and (12.5%) in DIG group. In conclusion the patients with type O are more likely to have diabetes and atherosclerosis, and those with type B are more likely to develop diabetes. Type A and AB are less likely to develop sclerosis.